Taxes, income and economic mobility in Ireland New evidence from tax records data - Kennedy, Seán (OECD Economics Department Working Papers, 2015)
This paper analyses income inequality in Ireland using a new panel dataset based on the administrative tax records of the Revenue Commissioners for Ireland. High inequality at market incomes in Ireland by international standards appears to be driven by both ends of the income distribution. An analysis of income mobility over time shows it has been low at both ends of the income distribution, though it increased at the low end once the crisis began, reflecting the sharp deterioration of the labour market. The data confirms that the tax system is highly progressive at the high end of income distribution and the welfare system provides the most significant support to lower income deciles in Ireland. The redistributive function in the tax and benefit system was enhanced during the last decade, not only because more income support was necessitated with the crisis, but also because of steeper and more progressive tax rates. This working paper relates to the 2015 OECD Economic Survey of Ireland (www.oecd.org/eco/surveys/economic-survey-ireland